2020
DOI: 10.1002/adfm.202004684
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Microfibers of Elastomeric Nanocomposites for Fully Stretchable and Highly Sensitive Microfluidic Immunobiosensor Patch

Abstract: The on-body immunodetection of biomarkers in sweat would significantly augment the potential of wearable body-interfaced biosensors for self-testing but has been limited due to the difficulty of integrating liquid handling and immunobiosensing devices in a wearable platform. Herein, a stretchable microfluidic immunobiosensor (SMIB) patch with hollow microfibers of elastomeric nanocomposites for the highly sensitive on-body biosensing of neuropeptide Y (NPY), a stress biomarker, in human sweat is reported. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…56,57 The Nyquist plot (Figure 3c) shows the smaller arc radii of the nitridated Fe 0 materials than that of nZVI (Figure 3c), suggesting their lower charge-transfer resistance. 58 However, a limited difference in the arc radii was observed for the nitridated Fe 0 materials with different N contents, consistent with similar lattice constants (Figure 3b) and N speciation (Figure S4b) of these nitridated Fe 0 materials.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…56,57 The Nyquist plot (Figure 3c) shows the smaller arc radii of the nitridated Fe 0 materials than that of nZVI (Figure 3c), suggesting their lower charge-transfer resistance. 58 However, a limited difference in the arc radii was observed for the nitridated Fe 0 materials with different N contents, consistent with similar lattice constants (Figure 3b) and N speciation (Figure S4b) of these nitridated Fe 0 materials.…”
Section: Resultssupporting
confidence: 75%
“…As a rule of thumb, a larger lattice constant means a larger interatomic distance, where the valence electrons tend to be released more readily, that is, a lower band energy gap and a faster electron transfer. , A similar phenomenon was also found in the sulfidation of Fe 0 when sulfur was incorporated into the Fe 0 BCC structure . This enlarged lattice is consistent with the result of the EIS measurement, which could assess the electron conduction performance of materials. , The Nyquist plot (Figure c) shows the smaller arc radii of the nitridated Fe 0 materials than that of nZVI (Figure c), suggesting their lower charge-transfer resistance . However, a limited difference in the arc radii was observed for the nitridated Fe 0 materials with different N contents, consistent with similar lattice constants (Figure b) and N speciation (Figure S4b) of these nitridated Fe 0 materials.…”
Section: Resultssupporting
confidence: 74%
“…The 5d, which is defined as ΔZ/Z 0 (ΔZ = Z − Z 0 , where Z 0 is impedance without NPY and Z is impedance in the NPY concentration range of 1 fM to100 pM). Good linearity was observed with an LOD of 1.1 fM, which demonstrates the capability of detecting the NPY level in a real human sweat (0.14−0.67 pM), 19 superior to other electrochemical sensors in Table S5. The selectivity of the NPY sensor was investigated by successive addition of interference molecules including glucose, uric acid, urea, and cortisol to the artificial sweat solution, which resulted in a negligible current response, a confirmation of the high NPY selectivity.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…As a rich bioanalyte noninvasive biological fluid, sweat remains scarcely investigated in indexing cardiovascular health, especially through multimodal biomarker detection . It has been reported that Na + (30–90 mM), ascorbic acid (AA, 1–40 μM), and neuropeptide Y (NPY, 140–670 fM) levels in sweat can reflect cardiovascular health conditions. Na + plays an important role in maintaining a variety of intracellular activities. Abnormal Na + levels can lead to unstable intracardiac metabolism resulting in myocardial ischemia and arrhythmias. , AA shows the capability of preventing atherosclerosis formation, stimulating blood coagulation function, and declining lipid levels in the blood. , NPY is an expressive neurotransmitter capable of modulating the immune and metabolic responses associated with an atherosclerosis degree .…”
Section: Introductionmentioning
confidence: 99%
“…or metabolites (glucose, uric acid, etc.) in physiological fluids, which are closely related to health status. Most of the reported physiological pressure sensors are based on the deformation of sensory materials caused by physiological pressure that is transduced into electric signals like current, resistance, and capacitance. For example, a highly sensitive pressure sensor was developed by Someya and co-workers to monitor finger manipulation with negligible sensory interference . The wearable sensor was fabricated by sandwiching a parylene-coated polyurethane fiber layer by two Au nanomesh electrode layers.…”
Section: Introductionmentioning
confidence: 99%